Taxonomy and nomenclature of Kalanchoe beharensis (Crassulaceae subfam. Kalanchooideae), a variable, arborescent species from Madagascar, with reference to its horticultural derivatives - Smith, Gideon F. (Phytotaxa, 2023)
The Malagasy Kalanchoe beharensis (Crassulaceae subfam. Kalanchooideae) is a variable, arborescent species from which several morphological variants have been selected for preferential distribution through the horticultural trade, with most of these generally made available under cultivar names or at least monikers presented as cultivar names. However, it is likely that some of the monikers presented as cultivar names have not been established as such under the International Code of Nomenclature for Cultivated Plants (ICNCP or Cultivated Plant Code) and serve as trade designations or even as common names only. However, trade designations are not names regulated by the ICNCP. In addition, at least some established cultivar names attributed to K. beharensis, the species, were derived from hybrid material of which K. beharensis is one parent. An overview is presented of a selection of widely used, established and apparently not established, names usually presented as cultivar names that apply to material derived from K. beharensis found in horticulture. A selection of these is illustrated. Two Groups are established under K. beharensis, K. beharensis Hairy Group and K. beharensis Glabrous Group. The nomenclature and taxonomy of K. beharensis is revisited with special reference to infraspecific designations that have not been validly published.